THE USE OF QRIS PAYMENTS FOR ULOS WEAVERS IN SIGAOL VILLAGE, ULUAN DISTRICT, REGENCY. TOBA - Frederick Saroha Silaban; Pasaman Silaban; Sabriana Simanjuntak (Universitas Pelita Harapan, 2024)
Digitalization has penetrated into various aspects of life, including in financial transactions. This community service aims to help ulos weavers in Sigaol Village, Uluan District, Toba Regency, in adapting to the use of digital payments through QRIS (Quick Response Code Indonesian Standard). This program uses a socialization and hands-on training approach. The socialization was carried out to provide a basic understanding of QRIS and its benefits, while the direct training was focused on how to use the QRIS application in daily transactions. In addition, technical assistance is also provided to ensure that weavers can use this technology smoothly. Results With the implementation of QRIS payments, ulos weavers in Sigaol Village can make transactions digitally more easily and quickly. This not only makes the payment process more practical, efficient, and effective, but also increases financial inclusion and strengthens the local economy. Through this activity, weavers are expected to be able to increase their competitiveness in a wider market, while authors get the opportunity to contribute directly to community empowerment.